Interação genotipo-ambiente para idade ao primeiro parto, perímetro escrotal e peso ao sobreano em bovinos da raça Nelore utilizando normas de reação - Chiaia, Hermenegildo Lucas Justino [UNESP] (2014)
Reducing the age at first calving (IPP) is directly linked to the efficiency and profitability of beef production. Despite its importance, the characteristics linked to early sexual activity in females, have been little used in breeding beef cattle programs in Brazil, as a consequence of its low heritability and low rate of selection in females. The scrotal circumference (PE) and IPP are easy to measure and the most important indicator of age at puberty in cattle. The yearling weight (PS) plays an important role in the genetic improvement to be the closest weight of slaughter weight. Currently, in Brazil, are published several summaries for Nelore bulls with various traits of economic importance, including all large data sets of animals distributed in various regions of the country. In cattle, there is no studies of genetic correlations of these traits on genotype-environment interaction (IGA). The objective of this study was to verify the genotype-environment interaction on the age at first calving, scrotal circumference and yearling weight in Nelore cattle, using multitrait random regression models. Data were collected on properties located in the North, Northeast, Midwest, and Southeast of Brazil participating in the Program for Genetic Improvement of Conexão Delta G. Environmental groups (AGs) were defined in relation to animals born in the same herd and year, management group (birth, weaning and yearling) and the same sex for IPP, PE and PS. The average gain after weaning weight was used as an environmental gradient. For the analysis of reaction norms linear Legendre polynomials regressed on GAs to model the additive genetic effects were used. Linear Legendre polynomials were used to model also fixed effect of the average population trend. The residual variances were modeled in homogeneous classes. The (co)variances were estimated using the software Wombat. The model for PE and PS included ...